Implementasi Pemberdayaan Masyarakat melalui Program GEULIS (GEnder Unggul LIngkungan organiS) di Kelurahan Klampis Ngasem - Zalman Alfarizt; Heny Sulistiana; Gideon Setyo Budiwitjaksono; Faizah Maulanda Salsabilla; Clara Oktavia Firdaus; Berlianto Juan; Shasa Nadia Kartikawati; Khalifah Mur Istifarih; Argya Bratasena; Regita Cahyani; Septia Anggraini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Empowering the community can lead to sustainable development. GEULIS (Excellent Gender and Organizational Environment) is a program that combines the principles of gender equality with environmental sustainability practices. GEULIS (Excellent Gender and Organizational Environment) program is in line with the sustainable development goals of Global SDGs 5, which concern gender equality and empowering women, and Global SDGs 15, which concerns protecting terrestrial ecosystems. This activity uses a qualitative approach with phenomenological methods to understand and analyze the experiences and perceptions of the Great Surabaya Cadre (KSH) RW 04 Klampis Ngasem Village regarding the GEULIS (Excellent Gender and Organizational Environment). Three methods were used to collect data: participant observation, semi-structured interviews, and documentation. Gender equality socialization aims to provide a broad understanding and view that women have equal rights and opportunities in various fields, such as politics, economics, education, society, culture, defense, and security. The workshop on making liquid organic fertilizer aims to increase public awareness regarding the use of waste, improve skills and economic opportunities, and encourage community participation in sustainably preserving the environment.